2019
DOI: 10.1097/tgr.0000000000000241
|View full text |Cite
|
Sign up to set email alerts
|

Functional Fitness in Older Adults

Abstract: Background: Using multiple interventions can increase muscle strength in older adults. A functional fitness test is a useful instrument to identify the effectiveness of physical functioning among older adults. However, the results in previous studies with regard to improvements in their physical function are inconsistent. Aim: To synthesize the intensity and interval of the effective interventions on physical functioning in community-dwelling older adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“… PubMed, EMBASE, Scopus, Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, Wan Fang, manual search of Soochow University and Nanjing University of Chinese Medicine libraries to March 2021 2003–2020 I: Traditional Chinese medicine-based exercises including but not limited to Tai Chi, Ba Duan Jin, and Qigong C: Placebo, AT, routine care, or educational programs 27 RCTs Inclusion: ≥55 Range: 59.7–88.8 2580 68 Moderate (Cochrane) Wirth 2020 [ 85 ] To investigate the effect of protein supplementation on body composition and muscle function in healthy adults. PubMed, Web of Science, CINAHL, Embase to March 2019 2001–2019 I: Oral protein intake, 2wk minimal duration, including energy-restriction or not, and including exercise or not C: Low-protein diet, no protein supplementation, or non-protein placebo 23 RCTs Inclusion: > 55 Range: 55–81 1290 62 Moderate certainty (GRADE) Yang 2019 [ 86 ] To determine intensity and interval of effective interventions in improving physical function in community-dwelling older adults. PubMed, EBSCO, and Cochrane Trials, Jan 1, 2013-Dec 31, 2017.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… PubMed, EMBASE, Scopus, Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, Wan Fang, manual search of Soochow University and Nanjing University of Chinese Medicine libraries to March 2021 2003–2020 I: Traditional Chinese medicine-based exercises including but not limited to Tai Chi, Ba Duan Jin, and Qigong C: Placebo, AT, routine care, or educational programs 27 RCTs Inclusion: ≥55 Range: 59.7–88.8 2580 68 Moderate (Cochrane) Wirth 2020 [ 85 ] To investigate the effect of protein supplementation on body composition and muscle function in healthy adults. PubMed, Web of Science, CINAHL, Embase to March 2019 2001–2019 I: Oral protein intake, 2wk minimal duration, including energy-restriction or not, and including exercise or not C: Low-protein diet, no protein supplementation, or non-protein placebo 23 RCTs Inclusion: > 55 Range: 55–81 1290 62 Moderate certainty (GRADE) Yang 2019 [ 86 ] To determine intensity and interval of effective interventions in improving physical function in community-dwelling older adults. PubMed, EBSCO, and Cochrane Trials, Jan 1, 2013-Dec 31, 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Included reviews reported on several types of interventions, with some reporting separate results for more than one intervention type. Most reviews focused on exercise or PA only ( n = 53) [ 26 35 , 37 40 , 42 , 44 , 45 , 47 , 49 – 75 , 77 , 78 , 80 – 84 , 86 ], while others included exercise with nutritional supplements ( n = 9) [ 25 , 36 , 41 , 43 , 46 , 48 , 76 , 79 , 85 ]. No reviews included group-based nutrition interventions alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical condition assessment included HG, lower body muscle strength, gait speed and agility/dynamic balance [ 23 , 55 , 56 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…As regular physical activity is a viable means of maintaining/improving the functional fitness of older adults (9), the second Physical Activity Guidelines for Americans in 2018 recommend that older adults above the age of 65 years engage in at least 150 min per week of moderate-intensity physical activity (PA) (10). However, several factors may affect older adults' intention to participate in exercise, such as the weather or the distance between their residence and the place they exercise (11).…”
Section: Introductionmentioning
confidence: 99%